Foliar application of a mixture of putrescine, melatonin, proline, and potassium fulvic acid alleviates high temperature stress of cucumber plants grown in the greenhouse - Yu Wang; Hongyun Liu; Weizhu Lin; Mohammad Shah Jahan; Jian Wang; Jin Sun; Jiankang Jiang; Weiyong Gu; Jiarong Zou; Sheng Shu; Shirong Guo (Technology in Horticulture)
Putrescine (Put), melatonin (MT), proline (Pro), and potassium fulvic acid (MFA) are widely used as plant growth regulators to enhance stress tolerance. However, the roles of their mixtures in response to stress are largely unknown. Here, we mixed Put with MT, Pro, and MFA (hereafter referred to as Put mixture) with different concentrations and foliar sprayed at different growth stages (seedling, flowering, and fruiting stage) of cucumber (Cucumis sativus L.) to investigate their roles on plant growth, fruit yield, and quality under high temperature stress. The foliar application of the Put mixture promoted cucumber growth, increased chlorophyll and Pro contents and net photosynthesis rate, and reduced the values of relative electrolyte leakage, H2O2 and malondialdehyde contents of cucumber leaves, indicating that treatment with Put mixture reduced the oxidative stress caused by high temperature. Furthermore, Put mixture-treated cucumber plants had lower fruit deformity rate and higher fruit yield compared with control. The contents of vitamin C and soluble solids of cucumber fruit significantly increased and the contents of tannin and organic acid decreased. The most profound effects were found in the plants treated with 8 mmol L−1 Put, 50 µmol L−1 MT, 1.5 mmol L−1 Pro and 0.3 g L−1 MFA every 7 d, three times at the seedling stage, indicating that cucumber seedlings treated with the mixture of Put, MT, Pro, and MFA significantly alleviated the negative effects of high temperature stress.